2020
DOI: 10.3390/s20092532
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Varroa destructor Infestation Classification Using an E-Nose Depending on the Time of Day

Abstract: Honey bees are subject to a number of stressors. In recent years, there has been a worldwide decline in the population of these insects. Losses raise a serious concern, because bees have an indispensable role in the food supply of humankind. This work is focused on the method of assessment of honey bee colony infestation by Varroa destructor. The approach allows to detect several categories of infestation: “Low”, “Medium” and “High”. The method of detection consists of two components: (1) the measurements of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 44 publications
(67 reference statements)
0
21
0
Order By: Relevance
“…Oates et al [ 46 ] presented research on a sinusoidally heated e-nose applied to olive oil type classification. Recently, several constructions were reported by Gonzalez Vieyo et al [ 47 ] to assess aroma profiles of beer, by Anyfantis and Bliona [ 48 ] to detect human presence, by Wu et al [ 49 ] for cigarette brand identification, and by Szczurek et al [ 50 ] to detect bee colony infestation. Development of a portable electronic nose for detection of pests and plant damage has been reported by Lampson and coworkers [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oates et al [ 46 ] presented research on a sinusoidally heated e-nose applied to olive oil type classification. Recently, several constructions were reported by Gonzalez Vieyo et al [ 47 ] to assess aroma profiles of beer, by Anyfantis and Bliona [ 48 ] to detect human presence, by Wu et al [ 49 ] for cigarette brand identification, and by Szczurek et al [ 50 ] to detect bee colony infestation. Development of a portable electronic nose for detection of pests and plant damage has been reported by Lampson and coworkers [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…The recent development and adaptation of gas sensor systems to beekeeping practices is really promising. They have already been used to infer a parasite pressure based on volatils detected in hives [ 256 , 257 ]. It is necessary to be able to precisely assess the state of the colony when infested with the acari, thus to use acaricides only if required and at the right moment [ 175 , 257 ].…”
Section: From the Laboratory To The Field: How To Be Realistic?mentioning
confidence: 99%
“…There is a high probability of obtaining misleading information when the measuring session is performed in an inadequate time period. This problem is mainly associated with the temporal variability of beehive air [26]. The chemical composition of air inside the beehive presents a temporal variability, see Figure 6.…”
Section: Consideration Of Temporal Factors Influencing Operation Of Gas Sensing Devices In Beekeepingmentioning
confidence: 99%
“…The important issue is also the time of the day when the measuring sessions should be performed. It was demonstrated that the adequate time of sampling and measurements allows to obtain better effectiveness of bee disease detection [26]. This knowledge is important from an economical point of view because it helps in planning an effective sampling program for the whole apiary.…”
Section: Consideration Of Temporal Factors Influencing Operation Of Gas Sensing Devices In Beekeepingmentioning
confidence: 99%